GE_GERICHTE P/2505/2016 vom 20. Februar 2017 - GE Cour de justice (2017)
SÉJOUR ILLÉGAL ; SURSIS À L'EXÉCUTION DE LA PEINE ; PRONOSTIC ; COMMERCE DE STUPÉFIANTS | LStup19.1 LEtr115.1.b CP47 CP49 CP41 CP42.2